Thinking ethnographically / Paul Atkinson. - Atkinson, Paul, 1947- (SAGE, 2017)
Introducing the idea of 'granular ethnography', this interdisciplinary text shows readers how to take ethnography's theoretical foundations into account and clearly lays out the importance of doing so.